СELL GROWTH FACTORS IN TISSUES OF THE EYE AFTER ANTIGLAUCOMA SURGERY USING CRYOPRESERVED HUMAN AMNIOTIC MEMBRANE - Kazmiruk, I.L. (World of Medicine and Biology, 2016)
A method of using the cryopreserved human amniotic membrane of the placenta has been studied by measuring in different tissues of body cell growth factors BDNF and 1b-TGF at different observation times. Cryopreserved AMCH used as a coating after antiglaucoma surgery. Measured content of biologically active substances in body tissues antigluakomatoznoy vision after surgery, it is shown that there is a qualitative and quantitative relationship accumulation BDNF and 1b-TGF cell growth factors, the type of eye tissue tropism according to cell growth factor.
Keywords: human amniotic membrane; cryopreservation; cell growth factors; antyhlaukomatozna operation